Analysis of Seagrass Nutritional Content of Enhalus acoroides (L.F.) Royle at Jelok Kete Beach, Jerowaru District, East Lombok, Indonesia - Muhammad Zulpadli; Firman Ali Rahman; Ervina Titi Jayanti (Ecobios Journal Of Environmental Science, 2024)
Enhalus acoroides (L.F) Royle seagrass is one type of seagrass that has an important ecological role in maintaining the balance of coastal ecosystems. However, research on the nutritional content of seagrass is still very limited, especially in the East Lombok region. This study aims to analyze the nutritional content of Enhalus acoroides (L.F) Royle seagrass fruit growing on Jelok Kete Beach, Batu Nampar, Jerowaru District, East Lombok. This study uses a descriptive quantitative approach. The method used includes sampling seagrass fruits at the research site and analyzing the laboratory to determine the nutritional content such as ash content, water content, carbohydrates, proteins, fats, and vitamins. The results showed that  the fruit of Enhalus acoroides (L.F) Royle has a nutritional content of 11% water content, 50% ash content, 7.87% protein, 10% fat, 21.2% carbohydrates, 7.74% vitamin c, and 2.67% chlorophyll-a levels.